Pengaruh disiplin kerja, pengembangan karir dan kompensasi terhadap kinerja pegawai direktorat protokol dan konsuler - Kukuh Bagus Panuntun; Masydzulhak Djamil (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
This study aims to determine the impact of work discipline, career development, and compensation on the performance of the civil servant (PNS) of the General Directorate Protocol and Consular Affairs. The research object is selected because there are still problems in performance goals, work discipline, compensation and career development. This is a quantitative study and data collection conducted within the General Directorate of Protocol and Consular Affairs using questionnaires, interviews, and documents. Data analysis used the structural equation analysis (SEM) method on the smartpls 3.3.3 software. The results of this study show that career development variables significantly impact on compensation, while work discipline, career development and compensation variables have a significant direct impact on performance. Then work discipline and salary variables mediated by compensation variables also have a significant impact on employee performance